A Case of Toxic Epidermal Necrolysis Secondary to Acetaminophen in a Child - æ#129;. Pena, María; Pérez, Sonia; Concepción Zazo, Mª; J. Alcalá, Pedro; D. Cuello, Juan; Zapater, Pedro; Reig, Roberto (Current Drug Safety, 2016)
Objective: To report and discuss a serious cutaneous adverse reaction in a child who was treated with acetaminophen (paracetamol). Case Summary: A five years old male child presented a pruriginous maculopapular rash and a “druginduced Stevens-Johnson syndrome/Toxic Epidermal Necrolysis” was suspected. Applying Spanish Pharmacovigilance System probability algorithm (modified Karch-Lasagna algorithm) for the suspected drugs (acetaminophen, ibuprofen and azithromycin), the causality of this adverse reaction was possible for acetaminophen and unlikely for the other two drugs. In this case it was recommended suspending and avoiding treatment with acetaminophen. This adverse reaction was reported to the Spanish Pharmacovigilance System (notification number: 10-600428). Discussion: Skin adverse reactions induced by drugs are uncommon but often serious and potentially fatal. There are few cases reports of “Stevens-Johnson syndrome/Toxic Epidermal Necrolysis” associated with acetaminophen in the literature. We present a documented case in a child. According to modified Karch-Lasagna algorithm, this case represents a possible adverse reaction. Conclusion: Hypersensitivity reactions with skin involvement are rarely associated with acetaminophen ingestion, but in a population such as the paediatric population, in which its use is widespread, the involvement of this drug should always be suspected if no other possible cause at sight.
Keywords: paracetamol